Pengaruh Model Pembelajaran Problem-Based Learning (PBL) Terhadap Keaktifan Dan Hasil Belajar Kognitif Siswa KelaS X Putri MA Miftahul Ulum Bettet Pamekasan - Moch. Haikal; Badriyatul Khoiriyah; Lukluk Ibana; Akhmad Fathir (Wacana Didaktika, 2022)
This study aims to determine the significant effect of the Problem Based Learning learning model on the activeness and cognitive learning outcomes of students of class X MA Putri Miftahul Ulum Bettet Pamekasan. This research is a quantitative research that uses a quasi-experimental research design with a non-equivalent pretest-posttest control group design. The sample of this research is class X IPS H as control class and X IPS G as experimental class. The mean control class activity score is M=45.7 and SD=6.36. The mean experimental class activity score is M=46.3 and SD=7.89. The results of the Kruskal-Wallis test showed that different learning models did not have a significant effect on student activity (χ²(1)=0.00836, p<0.001). The mean of control class learning outcomes is M=94.1 and SD=2.72. The mean of experimental class learning outcomes M=93.2 and SD=3.00. The results of the Linear Mixed Effects test showed that different learning methods did not have a significant effect on critical thinking skills (LRT(2)=4.86; p=0.088). The results of this study indicate that 1) there is no significant effect of the PBL learning model on the learning outcomes of class X students at MA Miftahul Ulum Bettet Pamekasan; 2) there is no significant effect of the PBL learning model on the activity of class X students at MA Miftahul Ulum Bettet. Keywords: Activity, Cognitive learning outcomes, Problem-Based Learning Abstrak: Penelitian ini bertujuan untuk mngidentifikasi adanya pengaruh signifikan model pembelajaran Problem Based Learning terhadap keaktifan dan hasil belajar kognitif siswa kelas X MA Putri Miftahul Ulum Bettet Pamekasan. Penelitian ini merupakan penelitian kuantitatif yang menggunakan design penelitian quasi eksperimen dengan rancangan non-equivalent pretest-posttest control group design. Sampel penelitian ini adalah kelas X IPS H sebagai kelas kontrol dan X IPS G sebagai kelas eksperimen. Rerata skor keaktifan kelas Kontrol M=45,7 dan SD=6,36. Rerata skor keaktifan kelas Eksperimen M=46,3 dan SD=7,89. Hasil uji Kruskal-Wallis menunjukkan bahwa dengan model pembelajaran yang berbeda tidak memberikan pengaruh yang signifikan terhadap keaktifan siswa (χ²(1)=0,00836, nilai p<0,001). Rerata hasil belajar kelas Kontrol M=94,1 dan SD=2,72. Rerata hasil belajar kelas Eksperimen M=93,2 dan SD=3,00. Hasil uji Linear Mixed Effects menunjukkan bahwa dengan model pembelajaran yang berbeda tidak memberikan pengaruh yang signifikan terhadap kemampuan berpikir kritis (LRT(2)=4,86; p=0,088). Hasil penelitian ini menunjukkan bahwa 1) tidak ada pengaruh signifikan model pembelajaran PBL terhadap hasil belajar siswa kelas X di MA Miftahul Ulum Bettet Pamekasan; 2) tidak ada pengaruh signifikan model pembelajaran PBL terhadap keaktifan siswa kelas X di MA Miftahul Ulum Bettet.